2016
DOI: 10.1186/s12888-016-1081-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of trauma-affected refugees with venlafaxine versus sertraline combined with psychotherapy - a randomised study

Abstract: BackgroundThe prevalence of trauma-related psychiatric disorders is high among refugees. Despite this, little is known about the effect of pharmacological treatment for this patient group. The objective of the present study was therefore to examine differences in the effects of venlafaxine and sertraline on Post-Traumatic Stress Disorder (PTSD), depression and functional impairment in trauma-affected refugees.MethodsThe study was a randomised pragmatic trial comparing venlafaxine and sertraline in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…A previous cross-sectional study from Norway has found particularly high rates of comorbid depression with PTSD in multi-traumatized refugees in outpatient clinics [30]. Similar results have been found internationally [33]. In our study, however, we were able to compare the types of disorders among the refugees with those of the native Norwegian population and other immigrants in the same clinical setting.…”
Section: Disorders After Traumasupporting
confidence: 79%
“…A previous cross-sectional study from Norway has found particularly high rates of comorbid depression with PTSD in multi-traumatized refugees in outpatient clinics [30]. Similar results have been found internationally [33]. In our study, however, we were able to compare the types of disorders among the refugees with those of the native Norwegian population and other immigrants in the same clinical setting.…”
Section: Disorders After Traumasupporting
confidence: 79%
“…A difference of less than ½ SD was considered less relevant from a clinical perspective. However, due to a smaller number than expected of male patients with a high HTQ score (which we stratified for in accordance with the average level of HTQ-score in previous RCTs conducted at CTP [24,25]) a larger number was included. Thus, the final number of included patients was 338.…”
Section: Discussionmentioning
confidence: 99%
“…The trial was conducted at the Competence Centre for Transcultural Psychiatry (CTP), a specialist outpatient clinic treating traumaaffected refugees in the Capital Region of Denmark. Since 2009, CTP has been conducting a series of randomised controlled pragmatic trials [24][25][26]. The target population at CTP comprises trauma-affected refugees (approximately 75%) and migrants with other psychiatric illnesses (approximately 25%).…”
Section: Methodsmentioning
confidence: 99%
“…Resettled refugees are vulnerable to development of mental illness due to multiple adverse life events, such as traumatic experiences and psychosocial stressors before, during and after flight (Kirmayer et al., ; Steel et al., ). Trauma‐affected refugees resettled in Denmark can exhibit delayed treatment‐seeking patterns, on average 15 years after traumatic exposure (Palic, Kappel, Nielsen, Carlsson, & Bech, ; Sonne, Carlsson, Bech, Elklit, & Mortensen, ). Thus, they often display chronic and complex psychiatric comorbidity, as well as high levels of disability (Palic et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Trauma-affected refugees resettled in Denmark can exhibit delayed treatment-seeking patterns, on average 15 years after traumatic exposure (Palic, Kappel, Nielsen, Carlsson, & Bech, 2014;Sonne, Carlsson, Bech, Elklit, & Mortensen, 2016). Thus, they often display chronic and complex psychiatric comorbidity, as well as high levels of disability (Palic et al, 2014).…”
Section: Introductionmentioning
confidence: 99%